2014
DOI: 10.1159/000354623
|View full text |Cite
|
Sign up to set email alerts
|

Categorizing Intraoperative Complications of Retrograde Intrarenal Surgery

Abstract: Purpose: To review our intraoperative complications of retrograde intrarenal surgery (RIRS) for kidney calculi and stratify these complications according to the modified Satava classification system (SCS). Patients and Methods: 230 patients (119 males, 111 females) who underwent RIRS because of kidney calculi were analyzed. We documented and stratified the intraoperative complications according to the modified SCS. There are four grades for this classification: grade 1 complications include events without cons… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
14
0
5

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 33 publications
(21 citation statements)
references
References 16 publications
2
14
0
5
Order By: Relevance
“…[1][2][3][4][5][6] The RIRS procedure can be considered as a safe method due to rarely occurence of major complications as classified according to Satava III or Clavien III-V criteria. [7,8] Only a limited number of studies so far have investigated the complications developed after RIRS, and they only presented some severe complications of the procedure. [3,5,6] But none of them investigated the postoperative pain as a complication, because it is a rather subjective symptom.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…[1][2][3][4][5][6] The RIRS procedure can be considered as a safe method due to rarely occurence of major complications as classified according to Satava III or Clavien III-V criteria. [7,8] Only a limited number of studies so far have investigated the complications developed after RIRS, and they only presented some severe complications of the procedure. [3,5,6] But none of them investigated the postoperative pain as a complication, because it is a rather subjective symptom.…”
Section: Discussionmentioning
confidence: 99%
“…[3,5,6] But none of them investigated the postoperative pain as a complication, because it is a rather subjective symptom. A classification system has been used for categorizing intraoperative complications of RIRS by using modified Satava classification system for the first time, recently [7] , however because the study was designed in a retrospective nature, colic pain was not evaluated as a complication. To our knowledge, there is not any publication focusing on the postoperative pain and associated factors after flexible ureteroscopy, and the present one is the first study about this topic.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…No difference was found in regards of postoperative complications and readmission rates between semi-rigid and flexible URS groups. [52] Oguz et al [53] reported rate of intraoperative complications as 30.4% according to modified Satava classification system. Grade 1, 2a and 2b complications were documented in 15.9%, 5.6% and 8.9% of the patients respectively, where no grade 3 complication was observed.…”
Section: Contraindications and Complicationsmentioning
confidence: 99%